2017
DOI: 10.1021/acsphotonics.6b01005
|View full text |Cite
|
Sign up to set email alerts
|

Metafabrics for Thermoregulation and Energy-Harvesting Applications

Abstract: Metafabrics are textiles with engineered constituent elements, possessing peculiar properties, which cannot be achieved with conventional fabrics. Fabric structures are formed of fibers bundled up and twisted into yarns. Yarns are then intertwined or bond closely together to shape the fabric structure. Engineering the textiles can be performed by utilizing novel materials for constitutive fibers and also manipulating the size and structure of fibers and yarns. In this paper, we employ a powerful and realistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Besides, the fiber cross section also influences the thermal radiation. [97,98] It is found that the textile woven with triangular polyamide (PA) fiber achieved a remarkable emissivity of 91.85%, better than the circular fiber with emissivity of 81.72%. This is because that the triangular fibers have different orientations inside a single yarn, benefiting for the absorption (and emission) of incident IR radiation from different directions with a higher efficiency.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Besides, the fiber cross section also influences the thermal radiation. [97,98] It is found that the textile woven with triangular polyamide (PA) fiber achieved a remarkable emissivity of 91.85%, better than the circular fiber with emissivity of 81.72%. This is because that the triangular fibers have different orientations inside a single yarn, benefiting for the absorption (and emission) of incident IR radiation from different directions with a higher efficiency.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The method has evolved quite dramatically ever since and has been adapted to solve several problems involving periodic and aperiodic arrangements of cylindrical objects [46][47][48][49] . In particular, the authors have extended the method to take into account for multiple scattering between cylinders and layered substrates 50 as well as crossed configurations of cylinders 51,52 . Here, we develop a novel semi-analytical framework by extending the T-matrix formulation to solve electromagnetic scattering from substrate-supported periodic and aperiodic arrays of cylindrical structures wrapped by time-varying graphene layers.…”
Section: Formulationmentioning
confidence: 99%
“…In the non-resonant Mie scattering region (effective medium regime) associated with deeply subwavelength microwires, they can be used to realize an effective refractive index by virtue of internal homogenization 3,15,52 . As such, time-modulated graphene-wrapped microwires can be used for realization of space-time gradient metamaterials and photonic crystals 69 .…”
Section: Time-modulated Metamaterials: Spatiotemporal Control Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating production is then generated from the human body radiation supplementary reflection that can even being increased by adding Joule heating to complement the passive insulation. For cooling purpose, recent papers have proposed different fibers [15][16][17][18] or membranes [19][20][21] fabrics to increase IR transparency. In the fiber configuration, Tong et al 15 proposed an infrared-transparent-visible-opaque-fabric (ITVOF) made of synthetic polymer fibers with intrinsically low IR absorbance and structured fibers to maximize IR transparency and visible opaqueness.…”
mentioning
confidence: 99%